Tesserae Intertext Service. - Nozomu Okuda; Kinnison, Jeffery; Burns, Patrick; Coffee, Neil; Scheirer, Walter (DHQ: Digital Humanities Quarterly, 2022)
The Tesserae Intertext Service Application Programming Interface (TIS-API) enhances the machine-accessibility of the intertext discovery capabilities of the Tesserae software. Instead of requiring inputs through a human-accessible webpage, the TIS-API accepts inputs according to a web development standard. Two case studies demonstrate the contributions of the TIS-API to computer-assisted literary criticism, particularly in increased software development and maintenance flexibility as well as in easier integration of Tesserae software into research workflows. Those interested in integrating the TIS-API into their digital projects can find documentation at https://tesserae.caset.buffalo.edu/docs/api/. For exact implementation details, the source code is available at https://github.com/tesserae/apitess.